2019
DOI: 10.3892/mmr.2019.10518
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA SLNCR1 regulates non‑small cell lung cancer migration, invasion and stemness through interactions with secretory phospholipase A2

Abstract: Long non-coding RNA (lncRNA) SRA-like non-coding RNA (SLNCR1; also known as linc00673) is a recently identified oncogenic lncRNA. The role of SLNCR1 in non-small cell lung cancer (NSCLC), a common malignancy, remains poorly understood. The present study aimed to investigate the involvement of long non-coding RNA SLNCR1 in the pathogenesis of NSCLC. Reverse transcription-quantitative PCR (RT-qPCR) and ELISA were performed to measure the levels of lncRNA SLNCR1 and secretory phospholipase A2 (sPLA2) in lung biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To date, an increasing number of lncRNAs is documented to be causally implicated in a variety of human disorders [11], including cancer. Among them, long intergenic noncoding RNA 673 (LINC00673), also referred to as SLNCR or SLNCR1, was discovered to be differentially expressed in many tumor types and to promote cancer development and progression through distinct molecular mechanisms [12][13][14][15][16][17][18][19][20][21][22]. Specifically, in spite of being noncoding, transcripts of LINC00673 can modulate chromatin dynamics and cancercausing gene expression by serving as a modular scaffold to interact with lysine-specific demethylase 1 (LSD1) and enhancer of zeste homolog 2 (EZH2) [14,16], recruiting androgen receptor (AR) and brain-specific homeobox protein 3a (Brn3a) to facilitate the expression of metalloproteinase 9 (MMP9) [13,21], stabilizing phosphorylation of dishevelled (Dvl) to activate WNT/β-catenin signaling [15], and acting as a competing endogenous RNA (ceRNA) for miR-150-5p [17], miR-515-5p [20], and miR-1231 [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, an increasing number of lncRNAs is documented to be causally implicated in a variety of human disorders [11], including cancer. Among them, long intergenic noncoding RNA 673 (LINC00673), also referred to as SLNCR or SLNCR1, was discovered to be differentially expressed in many tumor types and to promote cancer development and progression through distinct molecular mechanisms [12][13][14][15][16][17][18][19][20][21][22]. Specifically, in spite of being noncoding, transcripts of LINC00673 can modulate chromatin dynamics and cancercausing gene expression by serving as a modular scaffold to interact with lysine-specific demethylase 1 (LSD1) and enhancer of zeste homolog 2 (EZH2) [14,16], recruiting androgen receptor (AR) and brain-specific homeobox protein 3a (Brn3a) to facilitate the expression of metalloproteinase 9 (MMP9) [13,21], stabilizing phosphorylation of dishevelled (Dvl) to activate WNT/β-catenin signaling [15], and acting as a competing endogenous RNA (ceRNA) for miR-150-5p [17], miR-515-5p [20], and miR-1231 [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence has suggested that lncRNAs can participate in the regulation of various levels of chromosome modification, RNA transcription, and protein translation in physiological cell processes (Hon et al, 2017;Park et al, 2018;Podbevsek et al, 2018). In addition, lncRNAs can also have important effects on various stages of cell physiology (Misawa et al, 2016;Roisman et al, 2019;Xu et al, 2019). At the present time, a large amount of literature has shown that lncRNAs can regulate the development of bladder cancer in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the areas under the curve of Linc00673 in lung cancer 13 and pancreatic cancer 17 were found to be 0.683 and 0.6093, respectively. In addition to the tumor tissues, the corresponding trend of Linc00673 expression was also detected in the peripheral blood 17 , 30 . This study report suggests that Linc00673 may be a clinically effective biomarker for early molecular diagnosis.…”
Section: Linc00673 Expression In Tumor Tissues As a Molecular Markermentioning
confidence: 93%
“…LSD1, another important enzyme involved in epigenetic modifications, can also assist Linc00673 in promoting tumor progression via downregulating the expression of the tumor suppressor gene NCALD 13 . In addition, the high expression level of Linc00673 is also associated with the downregulation of the expression of opioid growth factor receptor (OGFR) 27 and the upregulation of the expression of secretory phospholipase A2 (spla2) 30 , although the molecular mechanisms involved in these events remain unexplored ( Figure 2 ).…”
Section: Mechanism Of Linc00673 In Cancersmentioning
confidence: 99%